MATHEMATICAL MODELING OF TEMPERATURE DISTRIBUTION IN THE MEMBRANE MODULE DURING MEMBRANE DISTILLATION - Ладієва, Л. Р.; Оніщенко, В. О.; Дубік, Р. М. (Science-based technologies, 2015)
The paper presents the mathematical model of the process contact membrane distillation. In recent years in the world of technology is widely implemented high salinity water desalination. The introduction of membrane technology is accompanied by a number of problems due primarily reliability and working resource membrane equipment. Using the installation process contact membrane distillation (KMD) requires a process control system. The proposed simplified mathematical model of KMD, which takes into account the change in the temperature of the solution and the distillate channel along the membrane and the membrane module height. As well as describing the change in temperature of steam flow in the pores of the membrane. An algorithm for calculating mathematical model of contact membrane distillation. Retrieved graph of temperature field distribution on the height of the membrane module at different distances from the input and transient response.